The jumping plant-lice (Hemiptera: Psylloidea) of Myanmar - Cho, Geonho; Lee, Seunghwan (Zootaxa, 2025)
The jumping plant-lice of Myanmar are reviewed based on material collected during recent expeditions by the Seoul National University (2016–2019) and published records. To date, only five psyllid species, viz. Ctenarytaina gravelyi, Diaphorina citri, Diceraopsylla brunettii, Pauropsylla depressa and Pseudophacopteron tuberculatum have been recorded from Myanmar. In this study, 21 species of 5 families, 10 subfamilies, and 16 genera are presented. Yangus burckhardti Cho sp. nov. is described from Myanmar. The new species is diagnosed and illustrated, and a key is provided to identify the adults of Yangus species in the world. The new species develops on Harrisonia perforata (Blanco) Merr. (Rutaceae), a liana species native to Southwest China to Tropical Asia. The distribution and host plants are provided for Myanmar based on museum material and published records.